Accidental Dural Puncture and Post-dural Puncture Headache in the Obstetric Population: Eight Years of Experience - Vaz Antunes, Maria (2016)
Introduction: Accidental dural puncture is an important complication of regional anesthesia and post-dural puncture headache remains a disable outcome in obstetric population. The aim of our study was to calculate the incidence of accidental puncture and post-puncture headache and evaluate its management among obstetric anesthesiologists.Material and Methods: We conducted a retrospective audit, between January 2007 and December 2014. We reviewed the record sheets of patients who experienced either accidental puncture or post-puncture headache. We excluded the patients undergoing spinal block. We use the SPSS 22.0 for statistical analyses.Results: We obtained 18497 neuro-axial blocks and 58 accidental dural punctures (0.3%). After detected puncture, in 71.4% epidural catheter was re-positioned and 21.4% had intra-thecal catheters. Forty-five (77.6%) developed headache and the prophylactic measures were established in 76.1%. Conservative treatment was performed in all patients. The epidural blood patch was performed in 32.8% with a 84.2% of success.Discussion: The incidence of post-dural puncture headache is unrelated to the type of delivery or insertion of intrathecal catheter. The re-placement of the epidural catheter remains the main approach after puncture. The institution of prophylactic measures is a common practice, despite the low level of evidence. We performed epidural blood patch after failure of conservative treatment.Conclusion: The incidence of accidental dural puncture and post-dural puncture headache was similar to the literature. Despite being a common complication, there remains lack of consensus on its approach.